REFORMULATING CARBON TAX IN INDONESIA: ADVANCING THE GREEN TAX REFORM IN CLIMATE CHANGE MITIGATION - Arifia, Septika Nanda; Novikasari, Siti Rahma; Perdana, Muhammad Anugerah; Maharani, Galuh Putri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Climate change mitigation has emerged as a pivotal global concern warranting considerable attention. In response to the escalating climate crisis, the "United Nations Framework Convention on Climate Change" (UNFCCC) has devised strategies aimed at mitigating climate change by curtailing carbon emissions. As a signatory to the UNFCCC, Indonesia has pledged to reduce carbon emissions by 29% to 41% by 2030 through collaborative efforts outlined in the Paris Agreement. Consequently, Indonesia is urged to develop an efficacious carbon tax policy to curb carbon emissions. Moreover, implementing a carbon tax could serve as the initial stride towards transitioning from fossil fuels to renewable energy sources. This research employs the normative juridical approach in its investigation. Findings reveal that Indonesia's carbon tax policy necessitates refinement to yield optimal outcomes aligned with its primary objectives. Hence, the author advocates for several reformulations of the carbon tax, offering them as potential frameworks or inspirations for enhancing the direction of the carbon tax policy.